Social Interaction on Early Childhood Expressive Language Development - Sumarni Jabir; Wahira Wahira; Andi Asrifan; Herlina Herlina (PT. Riset Press International, 2026)
Social interaction plays a crucial role in the development of children's communication skills. Social interaction is a relationship between two or more people in which the actions or behaviors of one individual can influence, change, or improve the actions or behaviors of other individuals, and vice versa. Children naturally learn through interactions with the people around them, including family members, peers, and their social environment. The intensity and quality of social interaction with the development of expressive language in children as an illustration, intensive verbal interaction in the family environment and early childhood educational institutions contribute significantly to the enrichment of vocabulary and verbal expression skills. This research aims to find out the form and social interaction on early childhood expressive language development. Research methods are quantitative, with an Ex Post Facto approach. The data collection technique in this study involved direct observation of the research sample. The data analysis techniques used are descriptive and inferential analysis. The results of the study show that social interactions influence the development of expressive language in early childhood. The results of simple linear regression analysis showed that social interaction had a positive and significant effect on the development of expressive language in early childhood. The form of social interaction that affects the development of expressive language in early childhood is children's interactions with peers and teachers during the learning process. The magnitude of the influence of social interaction on the development of early childhood expressive language is shown by the regression coefficient value of 0.892. This research is expected to provide a new perspective on research on children's language development, especially their expressive language. The use of new variables considered significant is expected to be a development in research on the object of study.